Strategi Peer Lessons dalam Meningkatkan Hasil Belajar Siswa pada Pelajaran Matematika di Kelas IV MI Negeri 1 Yogyakarta - Erni Yuliati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve students' learning outcomes with the implementation of Peer Lesson strategy for MIN 1 Yogyakarta students. This research uses the method of research actions carried out in two cycles, covering the planning, implementation, observation and reflection phases. The results showed that students' study results on an average I cycle of 69.3 increased to 78.9 in cycle II. The results of each cycle showed an increase in understanding the subject matter, in line with the development of activity and cooperation in the group. The average daily replay value has also increased with the average daily return of class from 71.2 to 79.42 after the implementation of Peer Lessons strategy. The implementation of Peer Lessons strategy can improve student learning outcomes.